2015
DOI: 10.1186/s10194-015-0555-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inflammatory mediators in the trigeminal ganglion by botulinum neurotoxin type A: an organ culture study

Abstract: BackgroundOnabotulinumtoxin type A (BoNT-A) has been found to reduce pain in chronic migraine. The aim of the present study was to ask if BoNT-A can interact directly on sensory mechanisms in the trigeminal ganglion (TG) using an organ culture method.MethodsTo induce inflammation, rat TGs were incubated for 24 hrs with either the mitogen MEK1/2 inhibitor U0126, BoNT-A or NaCl. After this the TGs were prepared for immunohistochemistry. Sections of the TG were then incubated with primary antibodies against CGRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Pilot studies of SPG injection of BoNT-A for treatment of CM as well as in chronic CH (CCH) have showed promising results [22, 23]. A previous study has shown presence of SV-2A and SNAP25 protein with same location in the TG [11]. The present results illustrate a possible site/mechanism of action for BoNT-A in CH.…”
Section: Discussionsupporting
confidence: 59%
“…Pilot studies of SPG injection of BoNT-A for treatment of CM as well as in chronic CH (CCH) have showed promising results [22, 23]. A previous study has shown presence of SV-2A and SNAP25 protein with same location in the TG [11]. The present results illustrate a possible site/mechanism of action for BoNT-A in CH.…”
Section: Discussionsupporting
confidence: 59%
“…OnabotulinumtoxinA mechanism of action is poorly understood. Recent studies have shown that OnabotulinumtoxinA is able to modulate the inflammatory mediators in the trigeminal ganglion [ 41 ] and decrease interictal CGRP plasma levels in patients with CM [ 42 ], and therefore be effective in the migraine attacks prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments that have proved efficacy in migraine patients, have been shown to prevent mechanical hyperalgesia in animal models [113,131]. For example, botulinum toxin could act peripherally inhibiting the release of a variety of neurotransmitters which are known to be key signaling molecules in CM including CGRP [132,133], so animal pre-treatment with botulinum toxin can prevent mechanical sensitization inhibiting mechanical nociception in peripheral trigeminovascular neurons [134]. For example, the mechanism of action of noninvasive vagus nerve stimulation for migraine treatment have also been investigated in the inflammatory soup model showing a decrease in periorbital sensitivity after de vagal stimulation [135].…”
Section: Animal Modelsmentioning
confidence: 99%